The Method of Fundamental Solutions for Steady-State Heat Conduction in Nonlinear Materials (Communications in Computational Physics, 2008)
The steady-state heat conduction in heat conductors with temperature dependent thermal conductivity and mixed boundary conditions involving radiation isinvestigated using the method of fundamental solutions. Various computational issuesrelated to the method are addressed and numerical results are presented and discussedfor problems in two and three dimensions.